Which equation is equivalent to the formula below? y = a(x – h)^2 + k ​

Question

Which equation is equivalent to the formula below?
y = a(x – h)^2 + k

in progress 0
Ivy 1 week 2021-11-26T03:47:19+00:00 2 Answers 0

Answers ( )

    0
    2021-11-26T03:48:37+00:00

    The photo provided by me has the answer attached.

    0
    2021-11-26T03:49:04+00:00

    Answer:

    See below.

    Step-by-step explanation:

    The given equation is in vertex form. We can convert it to standard form as follows:

    y = a(x – h)^2 + k

    y = a(x^2 – 2hx + h^2) + k

    y = ax^2 – 2ahx + (ah^2 + k)  (answer).

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )